ADVANCING ENERGY CONSERVATION AND SUSTAINABLE BUILDING PRACTICES THROUGH COMPREHENSIVE THERMAL-COOLING LOAD ANALYSIS IN AIRPORT BUILDING - Yulia, Fayza; Harianja, Valeska; Bonadharma, Nathan; Pajri, Noval; Irsan, Naufal (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2023)
The global discussion on conserving energy's importance has persisted, paralleling the surge in energy use over two decades. This rise presents challenges for local energy supply to diverse buildings. Designing energy-efficient buildings has become crucial in reducing energy usage and promoting sustainability. This research comprehensively analyzed and assessed thermal-cooling loads within an airport building using Panasonic software. The investigation primarily focuses on evaluating cooling load and thermal dynamics within the airport facility, emphasizing enhancing energy efficiency, and ensuring thermal comfort. Additionally, duct sizing design was conducted to achieve a comprehensive HVAC installation. From the result of the investigation, it was found that the highest Cooling Load at the airport occurs at 4:00 PM, aligning with the peak temperature resulting from heat transmitted into the building, reaching 263,591 Watts for the Airport Lounge and 82,202 Watts for the Luggage Room. Building energy management must be undertaken to minimize the energy consumption during that period. By thoroughly examining thermal-cooling loads within an airport building, this research contributes to decision-making for designing and operating HVAC systems, thereby advancing sustainable building practices.